The cloverleaf plate and proximal humerus fractures - Matiotti Neto, Mário; Rezende, Luis Guilherme Rosifini Alves; Andrade, Fernanda Ruiz de; Shimaoka, Filipe Jun; Mandarano-Filho, Luiz Garcia; Mazzer, Nilton; Barbieri, Cláudio Henrique (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Background: Fractures of the proximal humerus are challenging injuries. They have a functional impairment and can be managed by non-operative or operative methods. Surgical methods can be intramedullary nails, tension-band wiring, or plates and screws. Aim of the study: This study aims to show the outcomes of managing fractures of the proximal humerus using the trefoil plate method. Methods: Eight young patients with type 2 or 3 part proximal humerus fractures were retrospectively analyzed concerning the cloverleaf plate fixation and consolidation method. Patients with 4-part fractures were excluded. Results: We obtained 100% consolidation with a mean ROM of 109 degrees for abduction, 4.4 degrees for external rotation, and good internal rotation. Conclusion: the trefoil plate osteosynthesis method can be used in young patients with 2- or 3-part fractures of the proximal humerus.